Benign Coionic Ulcers: about 4 observations - Piacenza, Guillermo; Torterolo, Edgardo; Carriquiry, Luis; Acosta Ferreira, Walter; Viñuela, Enrique (Cirugía del Uruguay, 1980)
The series comprises 4 Benign Colonic Ulcers. The author reviews their frequency, etiologic aspects and clinical form. Anato·mopathoogy is analyzed and finally treatment is discussed: these steps are fundamental in determining prognosis.